Beta cell function as an assessment tool for cardiovascular risk in patients with metabolic syndrome - Erman, Hande; Böyük, Banu; Cetın, Seher Irem; Sevınc, Samet; Bulut, Umit; Maviş, Osman (Journal of Surgery and Medicine, 2021)
Background/Aim: Epicardial fat tissue (EFT) is considered a cardiovascular risk factor independent from visceral adiposity, obesity, hypertension, and diabetes. Fasting serum C-peptide is a known marker of endogenous insulin secretion and beta cell function. Our aim was to evaluate C- peptide levels in patients with metabolic syndrome (MetS) in relation to the EFT thickness. Methods: Forty-five subjects with MetS without a history of coronary artery disease and 25 healthy volunteers were enrolled this prospective case-control study. We examined the laboratory values, including C peptide, insulin, and HOMA-IR after 8 hours of fasting. EFT thickness was measured by two-dimensional transthoracic echocardiography. Results: The serum C peptide levels were significantly higher in patients with metabolic syndrome compared to the healthy controls [3.41(1.98) ng/ml vs 2.07 (1.39), P<0.001]. C peptide levels were correlated with BMI (P=0.03, r=0.281) and serum triglycerides (P=0.03, r=0.288). Patients with MetS had remarkably high EFT thickness [0.63(0.22) mm, P=0.043]. EFT thickness was correlated with age (P=0.008, r=0.397), weight (P=0042, r=0.308) and C-peptide (P=0.002, r=0.460) in patients with MetS. Conclusion: EFT thickness and elevated C-peptide are independent risk factors influencing atherosclerosis. The strong association between EFT thickness and C-peptide demonstrated herein indicates that EFT may play an important role in C peptide secretion, possibly contributing to the cardiometabolic risk in patients with MetS.